PERAN TRADISI DALAM TREND FORECASTING - Akbar Adhi Satrio; Tri Hasdianto Hasdianto; Amelinda Alysia A.V.K. (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2020)
This study is preliminary research of